(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to know the degree of faculty members presentation for educational scaffolding from the point of master’s students/ First year in the following areas (preparation, providing learning module, group-oriented practice, Increase learner responsibilities, directed feedback, independent practice). And revealing the differences in the students’ views about the degree to which teaching staff provide educational scaffolding according to the variables (academic specialization). To verify the objectives of the research, the descriptive approach was used, and a questionnaire was prepared for educational props, which consisted of (40) phrases, and was applied to the research sample, which consisted of (26) students from the master’s / first-year students in the Faculty of Education at Tishreen University, for the academic year 2021- 2022. The researcher reached several results, the most important of which are: - The teaching staff at the Faculty of Education in Tishreen University provide educational supports to a high degree, from the point of view of the master’s students / first year. - There are differences between the answers of the members of the research sample to the questionnaire on the degree to which faculty members provide educational supports according to the variable of academic specialization, between students of psychological counseling and both students of curricula, educational techniques and educational principles, in favor of students of psychological counseling, while there were no significant differences between other disciplines. Based on the results extracted from the research, several recommendations were made, the most important of which are: teaching staff provision of educational props while teaching first-year master’s students by granting them material and moral incentives, and conducting scientific research to study the effectiveness of using the educational props strategy in developing students’ thinking and research skills Master’s degree at the Faculty of Education in Tishreen University.